PERJUANGAN PEREMPUAN PADA MASA PEMBERONTAKAN DI/TII DALAM NOVEL AZIZAH KARYA EMMAH AZRA - Devi Setiawanti; Faika Burhan (Jurusan Ilmu Sejarah Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to describe the struggle of women during the DI / TII rebellion in the novel Azizah by Emmah Azra. This type of research is classified as library research. The research method used descriptive qualitative method. The research data were in the form of story texts relating to the structure of the novel and the struggle of women during the DI / TII rebellion in the novel of Azizah by EmmahAzra. The technique used in this study was the technique of reading and taking notes. The theory used to analyze the data in this study was Genetic Structuralism by Lucien Goldmann. Based on the results of this study it could be concluded that through the novel of Azizah by Emmah Azra, the author described the conditions and struggles of women. This novel described the lives of women during the DI / TII rebellion in South Sulawesi in the 1950s. The novel of Azizah by EmmahAzra also told about Kahar Muzakar's resistance in fighting for the application of Islamic law. Emmah also described the impact of the war on the lives of women and society at that time. At that time, society, especially women, had to move places to avoid war and save them. Keyword: Azizah's novel, Women's Struggle, Genetic Structuralism, and World View